2008
DOI: 10.1890/07-0521.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tillage Practices on Arbuscular Mycorrhizal Fungal Diversity in Subtropical Crops

Abstract: Arbuscular mycorrhizal fungi (AMF) are a main component of soil microbiota in most agrosystems. As obligately mutualistic symbionts, they colonize the roots of the majority of plants, including crop plants. We used molecular techniques to investigate how different tillage systems (moldboard, shred-bedding, subsoil-bedding, and no tillage) can influence the AM fungal community colonizing maize, bean, and sorghum roots in an experimental site located in northern Tamaulipas, Mexico. Roots from 36 plants were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
85
1
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(115 citation statements)
references
References 49 publications
17
85
1
12
Order By: Relevance
“…van der Heijden et al 2006;Maherali and Klironomos 2007). Several studies have shown that the composition and diversity of AM fungal communities in agricultural ecosystems depend on land use intensity, crop rotation, fertility level and tillage intensity (Alguacil et al 2008;Oehl et al 2003Oehl et al , 2004Hijri et al 2006). Hence, such differences in AMF community composition may also affect weed growth, if weeds respond differently to different AMF communities.…”
mentioning
confidence: 99%
“…van der Heijden et al 2006;Maherali and Klironomos 2007). Several studies have shown that the composition and diversity of AM fungal communities in agricultural ecosystems depend on land use intensity, crop rotation, fertility level and tillage intensity (Alguacil et al 2008;Oehl et al 2003Oehl et al , 2004Hijri et al 2006). Hence, such differences in AMF community composition may also affect weed growth, if weeds respond differently to different AMF communities.…”
mentioning
confidence: 99%
“…O preparo do solo é o mais direto e drástico estresse cultural que incide sobre a formação das micorrizas. A retirada da vegetação que acarreta na quebra do fluxo de exsudados radiculares e na disponibilidade de fotoassimilados, afeta a população de FMAs (COLOZZI-FILHO et al, 1999;CASTILHO et al, 2006;ALGUACIL et al, 2008 O sistema PDsem teve uma separação pela ACP pela colonização radicular total com um valor de |1,3263| e PRsem pelo atributo arbúsculo sendo esse com o maior valor |1,3546| (Tabela 3). Para PCA 2 nota-se que esta separa os tratamentos PCsem do PCinc (Figura 2), sendo que este último teve uma maior influencia das hifas com um valor de |0,7007| (Tabela 3).…”
Section: Resultsunclassified
“…A combinação do cultivo mínimo com plantas com alto grau de micotrofia empregadas em cobertura contribuem para manter elevada densidade de hifas, elevado potencial de inoculo, estabilização do solo e, assim, manter a sustentabilidade da produção (KABIR, 2005). A adubação com doses excessivas de fertilizantes, uso indiscriminado de defensivos e o revolvimento intensivo do solo, são práticas que afetam negativamente os FMAs, e assim contribuem para a reduzida sustentabilidade de sistemas que empregam estas práticas (ALGUACIL et al, 2008).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…토양의 미생물 활성을 나타내는 지표 는 미생물 생체량, 탈수소 효소 등이 있으며 최근에는 내생균 근균이 분비하는 당단백질인 글로말린 함량이 있다 (Gillespie et al, 2011;Rilling et al, 2005;. 일반적으로 글로말린 관련 토양 단백질은 토양 유기 물 함량의 5.4-21.2%를 차지하고 있으며 (Vodnik et al, 2008) 경운을 하게 되면 내생균근균의 개체수가 감소되어 글로말 린 함량이 낮아지는 것으로 알려져 있다 (Alguacil et al, 2008;Wright et al, 1999). 국내에서는 보리나 호밀을 처 리한 토양 보다 헤어리베치를 처리한 토양에서 글로말린 함 량이 높았고 (Jeon et al, 2010) 유기재배 토양이 관행재배 토양 보다 1.2배 높은 것으로 보고되었다 (Min et al, 2011).…”
Section: Introductionunclassified